Exploring sugar-induced cell death in yeast: implications for diabetes and cancer research - Parbhudayal, Raveena; Cheng, Hai-Ping (Frontiers in Cell Death, 2025)
When yeast cells are transferred to water only, they remain viable for several days. However, when transferred to water with glucose, there is a rapid loss of viability. This phenomenon is termed Sugar-Induced Cell Death (SICD). In addition to glucose, SICD can be induced by an array of different sugars and is thought to be triggered by increased levels of intracellular reactive oxygen species (ROS) generated upon transfer to sugar-only solutions. Although not termed SICD, a similar response is observed in mammalian cells, whereby high glucose induces cell death, especially in cases of hyperglycemia and diabetes. In contrast, cancer cells thrive under conditions of high glucose. In this review, we summarize the current understanding of SICD in yeast and highlight studies showing the presence of a similar phenomenon in mammalian cells, High Glucose-Induced Cell Death (HGICD). We end with a discussion on mechanisms by which cancer cells evade HGICD. Unlike other types of cell death in yeast, SICD has not yet been thoroughly reviewed. Therefore, this review represents the first comprehensive review of SICD in yeast with a comparison to HGICD in other eukaryotes.